Effectiveness of Fosfomycin against Extended Spectrum Beta-Lactamase Producing Escherichia coli in Urinary Cultures - Hareem Gohar et al; Faisal Iqbal Afridi; Madeeha Fatima; Ambreen Fatima; Nayab Afzal (ziauddin University, 2024)
Background: Urinary tract infections (UTI) considered, as the most frequently diagnosed infections constitute Escherichia coli (E. coli) as the most common etiological agents isolated from urinary cultures. Fosfomycin is becoming the best treatment option for UTI because of its rapid absorption, good concentration in urine. The present study aimed to determine and compare the susceptibility of Fosfomycin, presented as a favorable choice against E. coli producing extended spectrum beta-lactamase (ESBL) in urinary cultures of patients. Methods: This cross sectional study with non-probability consecutive sampling was held at Ziauddin University Hospital Microbiology Laboratory. A total of 222 urinary isolates of in and out patients yielding growth of ESBL positive E. coli were identified using standard microbiological technique. Susceptibility testing of antimicrobials was accomplished according to Clinical Laboratory Standard Institute (CLSI) guidelines. Detection of ESBL was done by double disk diffusion technique. Independent sample t-test was used to compare mean ages and Chi-squared test for the ESBL positivity in various age groups. A p-value of less than 0.05 was considered as statistically significant. Results: The mean age of the patients was 56.68±21.18 years. There were 59(26.58%) male and 163(73.42%) female. The sensitivity of ESBL producing E. coli to Fosfomycin was 94.59 % (210/222) which was much higher as compared to other antimicrobials, Meropenem (89%), Amikacin (83%) and Nitrofurantoin (78%). There was no statistically significant variance among the age groups with respect to fosfomycin susceptibility (p=0.601). Conclusion: Fosfomycin have high antimicrobial activity against ESBL positive E. coli in urinary samples. It could be a good treatment choice for urinary tract infections. Keywords: Urinary Tract Infections; Fosfomycin; Escherichia coli; Beta-Lactamases.